Asal-Usul Teologi: Pelacakan Historis Filosofis - Bilad, Cecep Zakarias El (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2018)
This study attempts to examine the origin of theology. In every religion, it is the most substantial element, because it is the intellectual discourse around the divinity and belief of that religion. We know the terms such as Christian Theology, Jewish Theology, Islamic Theology, Hindu Theology and so on. From here, howeover, it raises the question of what theology is intrinsically? Etymologically the term theology is in fact derived from the Greek whose people are the worshipers of the gods and do not recognize the conception of divinity as other religions do. How can it exist in these religions? From this historical-philosophical search it is found that theology in its generic meaning is defined as the discourse of the exalted supranatural being. It is born naturally in every society from time to time. It can take a variety of forms according to the religious tradition of its people, but in essence it is the discourse on the One who organizes and manages the universe.